Efficient Extracellular Production of α-Amylase in Bacillus subtilis under the Influence of Xylose-Inducible Promoter - Abd-El Aziem Farouk; Iqra Aroob; Quratulain Amjad; Hala Mohamed Abdelmigid; Ralf Greiner (BioResources, 2025)
This study focuses on the development of a xylose-inducible system to produce recombinant α-amylase from the bacterium Thermoactinomyces vulgaris 94-2A (amyTV) in the Bacillus expression system. To achieve this, a gene cassette was constructed using pWH1520 shuttle vector, containing a PxylA promoter comprising glucose box and amyTV gene. The cassette was initially cloned in Escherichia coli for replication and subsequently, introduced into the Bacillus subtilis (GSB26) for expression. To optimize the secretion of α-amylase, different concentrations of xylose were used as inducers. It was found that the maximum amylase activity was achieved when 2% xylose was used as the inducer. Furthermore, using glucose alone and in combination with xylose as inducers indicated that glucose acted as a catabolic repressor for amyTV expression. Moreover, protein was efficiently secreted and did not accumulate in the cellular fractions, even at high expression levels.